(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Chattogram City in Bangladesh is hyperendemic for dengue and is one of the leading districts in reporting deaths due to dengue. As primary prevention of dengue has had limited success, the prevention of mortality through the identification of risk factors and efficient patient management is of utmost importance. The current study aimed to identify clinical predictors of mortality in adult patients with dengue in a public tertiary level hospital in Chattogram, Bangladesh. Materials and methods: A record-based retrospective case-control study was conducted at Chittagong Medical College Hospital (CMCH). 46 (Forty six) death patients were included in the study as case and 46 age and sex matched survivors were enrolled as control who were admitted at CMCH during course of their illness. Demographic, clinical, and treatment-related factors were compared between the two groups. Most of the patients in the case group were admitted (47.6%) and expired (50%) during the evening shift (2.30-10.00 pm). Results: In multivariate analysis for predicting mortality, patients from rural areas [Odds Ratio (OR): 7.40, 95% Confidence Interval (CI):1.53-15.23, p=0.012], Dengue Shock Syndrome (DSS) at admission (OR:8.72, 95% CI:1.89-21.21, p=0.006) presence of comorbidity (OR:6.76, 95% CI:1.53-21.11, p=0.012), and patients complicated with respiratory failure (OR: 8.84, 95% CI:3.16-31.21, p=0.001) were associated with mortality in patients with dengue. Conclusion: The independent predictors of mortality were rural residence, DSS at admission, comorbidity and development of respiratory failure. Addressing these factors with more rigorously monitored treatment would likely reduce mortality. JCMCTA 2025 ; 36 (1) : 4-9